Energy and amino acid sources and levels for nursery and finishing swine diets - Royall, Rafe Quinnlan (My University, 2024)
The 5 chapters of this dissertation involve 1) determining the effects of dietary net energy (NE) concentrations on growth performance and carcass characteristics of finishing pigs and an evaluation of the accuracy of different ingredient databases and NE equations, 2) determining standardized ileal digestible (SID) threonine:lysine (Thr:Lys) requirement estimates for 11 to 120 kg pigs, 3) a review of dietary soybean meal (SBM) usage in growing and finishing pig diets, 4) evaluating the effects of 3 lactation feeder designs on sow and litter performance, and 5) determining the effects of replacing lactose with novel carbohydrate sources on nursery pig growth performance and feed intake preference. Chapter 1 utilized 1,927 finishing pigs to determine the effects of reducing NE and using this caloric efficiency (CE) data to estimate the accuracy of ingredient databases and NE equations. Results from this experiment suggest that reducing NE reduces finishing pig performance, the NE values from the CVB database and system of equations are the most accurate estimate of NE when CE is calculated based on live gain, while the values from the Brazilian Tables for Poultry and Swine are the most accurate when CE is calculated based on carcass gain. Chapter 2 consisted of 4 experiments involving 3,208 pigs were conducted to determine SID Thr:Lys ratio requirement estimates for average daily gain (ADG), gain to feed ratio (G:F), and blood urea nitrogen (BUN) throughout the late nursery, grower, and finisher phases. Dose-response models developed using the data from Exp. 1 and 2 predicted a requirement for ADG beyond the highest dose tested (68% SID Thr:Lys ratio), which led us to test a wider range of SID Thr:Lys ratios in Exp. 3 and 4. Data from Exp. 3 and 4 were combined and used to fit dose-response models which suggested that; ADG was maximized between 61.1 and 68.6% SID Thr:Lys ratio, G:F is increased up to 59.2% SID Thr:Lys with no improvement thereafter, and BUN was minimized at 69.2%. Additionally, these data may suggest that SID Thr:Lys requirements are similar for pigs from 37 to 70 kg and 96 to 120 kg. Chapter 3 consisted of a literature review over dietary SBM levels in various dietary and environmental situations. Soybean meal is a good source of amino acids and energy in the diet and contains biologically active compounds that can improve swine health and growth performance. Chapter 4 consisted of one experiment utilized 557 mixed parity sows to evaluate lactation feeder design on sow and litter performance, feeder cleaning criteria, and economic return. We observed that sows fed using the wet-dry feeder designs had increased feed disappearance with no effects on sow and litter performance compared to dry feeders, thus worsening litter feed efficiency and increasing feed cost per sow and litter. Chapter 5 consisted of 2 experiments which used 660 nursery pigs to determine the effect of replacing lactose in nursery pig diets with one of two novel carbohydrate products (CHO-D and CHO-L) on growth performance and feed intake preference. In Exp. 1, we found similar growth performance between all carbohydrate sources, but we were unable to detect benefits of adding lactose to the diet. In Exp. 2, we found that pigs preferred the diet containing CHO-D over the diet containing lactose in phase 1, but the inverse was true in phase 2. However, pigs preferred the diet containing lactose over the diet containing CHO-L in all phases. Thus, we could not determine whether the novel carbohydrate products are suitable replacements for lactose.
Keywords: Amino acid; Carbohydrate; Grow-finish pig; Lactation feeder; Net energy; Soybean meal